PENERAPAN SISTEM ADMINISTRASI PERPAJAKAN MODERN UNTUK MENINGKATKAN PENERIMAAN PAJAK DI INDONESIA PERIODE TAHUN 2000 SAMPAI DENGAN TAHUN 2009 - Pujiwidodo, Dwiyatmoko (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2009)
Abstract:With the economy growing in Indonesia and to create a clean government, the Directorate General of Taxes (DGT) feel the need to make the tax modernization. One form of tax modernization is the application of latest information technology in the service tax. This service improvement seen with the continued development of a modern tax administration and information technology in various aspects of activities from registration as tax payers via e-registration, tax payments (e-payment), tax reporting (e-reporting, e-SPT), pemberkasan tax documents (e-filing), and consultation (e-consulting), and so on. This modernization program carried out to achieve four main objectives. First, a fair revenue optimization is the expansion of tax base, tax minimization gaps and fiscal stimulus. Second, increase voluntary compliance through excellent service and consistent law enforcement. Third, administrative efficiency, the implementation of administrative systems and a reliable and efficient technology utilization. Finally, the formation of a good image and high public confidence in the capacity of human resource professionals, organizational culture that is conducive and the implementation of good governanceKeyword:Good Governance, Tax Modernization, Information Technology and Administration of Taxation